Natural products intervene in non-alcoholic fatty liver disease by regulating the AMPK signaling pathway: preclinical evidence and mechanism - Zhang, Chuyue; Shi, Jianing; Shi, Lijun (Frontiers in Pharmacology, 2025)
Non-alcoholic fatty liver disease (NAFLD) is characterized by core pathological features such as hepatic lipid accumulation, oxidative stress, and inflammatory responses. Its pathogenesis is closely associated with dysregulated energy metabolism. Adenosine monophosphate-activated protein kinase (AMPK), a central regulator of cellular energy homeostasis, ameliorates NAFLD-related lipid metabolic imbalance and liver injury by phosphorylating downstream target proteins (e.g., ACC, mTOR, SREBP-1c). This process suppresses fatty acid synthesis, promotes oxidative degradation, inhibits inflammasome activation, and enhances antioxidant capacity. Recent studies have identified reduced AMPK activity as a critical pathological hallmark of NAFLD. Targeted activation of the AMPK signaling pathway alleviates NAFLD progression through multiple mechanisms, including lipid metabolism regulation, anti-inflammatory effects, restoration of antioxidant capacity, and enhanced autophagy. Natural products derived from traditional Chinese medicine have shown significant potential in regulating the AMPK signaling pathway. Research indicates that Traditional Chinese Medicine (TCM) extracts (e.g., terpenoids, phenols, flavonoids, saponins, and alkaloids) can directly activate AMPK or regulate its upstream kinases (LKB1, CaMKKβ) and downstream effectors (SIRT1, PPARα, Nrf2), thereby improving hepatic lipid accumulation, mitigating inflammatory damage, and delaying NAFLD progression. By searching the databases of Web of Science, PubMed, Google Scholar and CNKI, and integrating the latest research progress, systematically summarizes the role of the AMPK pathway in NAFLD and the intervention mechanisms of natural products, aiming to provide a theoretical basis for the development of innovative traditional Chinese medicine drugs for NAFLD.